ADSORPTION OF CR ON LIQUID WASTE OF TANNERY INDUSTRY USING BANANA PEEL CHARCOAL IN VARIOUS PH AND TIME ACTIVATION - Atmasari, A. D.; Amaliya, F.; Puspitasari, L. (Indonesian Journal of Chemistry and Environment, 2019)
The purpose of the research is to determine the effect of activation time of banana peel charcoal on the adsorption capacity of Cr metal's tannery industry. Banana peel charcoal is made by carbonization process followed by activation using HCl solution with varying time. The activated charcoal with optimum activation time is used to determine the optimum pH of tannery waste on adsorption Cr metal. Banana peel as much as 600 grams then carbonized can form 42 grams of banana peel charcoal. The concentration of Cr metal initial that contained in tannery waste was 292.1 ppm. The optimum activation time is 1 hour, with decreasing Cr metal as much as 141.87 ppm using 1 gram of banana peel activated charcoal. While the pH variation of waste does not provide a significant difference.